2017
DOI: 10.5414/cp202629
|View full text |Cite
|
Sign up to set email alerts
|

A study comparing the safety and efficacy of febuxostat, allopurinol, and benzbromarone in Chinese gout patients: a retrospective cohort study

Abstract: Chinese patients treated with the 40-mg dose of febuxostat experienced a treatment effect and total rate of adverse events similar to those produced by allopurinol or benzbromarone. To achieve a better therapeutic effect, the dose of febuxostat can be elevated to 80 mg per day; however, patients receiving the higher dose must be closely monitored for signs of liver dysfunction. Febuxostat is an alternative treatment for Chinese gout patients who are at a much higher risk for severe cutaneous adverse reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…In our literature search, we found several other studies published in or after 2008 that directly or indirectly evaluated the safety of benzbromarone [19-21, 26, 28, 37-39]. Among these, a one-year prospective analysis of 123 patients in New Zealand and a three-year Chinese retrospective study both reported no serious events related to benzbromarone treatment [19,21]. Two other systematic reviews reported similar results [20,38].…”
Section: Studies Evaluating Benzbromarone's Safetymentioning
confidence: 86%
See 1 more Smart Citation
“…In our literature search, we found several other studies published in or after 2008 that directly or indirectly evaluated the safety of benzbromarone [19-21, 26, 28, 37-39]. Among these, a one-year prospective analysis of 123 patients in New Zealand and a three-year Chinese retrospective study both reported no serious events related to benzbromarone treatment [19,21]. Two other systematic reviews reported similar results [20,38].…”
Section: Studies Evaluating Benzbromarone's Safetymentioning
confidence: 86%
“…Several studies and meta-analyses have demonstrated benzbromarone's efficacy in reducing sUA levels and preventing gout flares. The usual dosage varies between 50 mg and 200 mg daily [16,[19][20][21].…”
Section: Efficacy Evidencementioning
confidence: 99%
“…Фебуксостат проявил значительную эффективность в сравнении с аллопуринолом в исследовании Q. Zhou et al (2017) [8]. Так, лечение фебуксостатом (40 мг) существенно снижало уровни МК в сыворотке у пациентов по сравнению с теми, которые получали аллопуринол или бензбромарон в средней терапевтической дозе.…”
Section: ключевые слова: подагра; гиперурикемия; мочевая кислота; ураunclassified
“…Most of the drugs selected in the clinical treatment are urate transporter selective inhibitors and xanthine oxidase (XOD) inhibitors. However, long-term use of drugs to inhibit the production or promote the excretion of uric acid, such as Febuxostat [17] (XOD inhibitors) and benzbromarone [18] (UA excretor) may cause a series of adverse reactions, including severe hypersensitivity [19] , and serious liver and kidney damage [20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the role of the intestine [20,21] in maintaining the homeostasis of UA level in the body has become the focus of attention. It has been found that the reduction of intestinal excretion of UA [23,24] is an important cause of HUA.…”
Section: Introductionmentioning
confidence: 99%